Community Composition, Antifungal Activity and Chemical Analyses of Ant-Derived Actinobacteria - Wang, Zhiyan; Yu, Zhiyin; Zhao, Junwei; Zhuang, Xiaoxin; Cao, Peng; Guo, Xiaowei; Liu, Chongxi; Xiang, Wensheng (Frontiers in Microbiology, 2020)
Actinobacteria associated with insects represent one potentially rich source of novel natural products with antifungal activity. Here we investigated the phylogenetic diversity and community composition of actinobacteria associated with ants using a combination of culture-dependent and -independent methods. Further, we assessed the antagonistic activity against phytopathogenic fungi and identified the secondary metabolites from isolates with bioactivity. A total of 416 actinobacterial isolates were obtained from three ant species located in five nests. The largest amount of isolates were observed in the head samples. 16S rRNA gene sequencing showed that the isolates were diverse and belonged to ten genera within the phylum Actinobacteria, with Streptomyces and Micromonospora comprising the most abundant genera. High-throughput sequencing analyses revealed that the actinobacterial communities were more diverse and dominated by the families Nocardioidaceae, Nocardiaceae, Dermacoccaceae, Intrasporangiaceae and Streptomycetaceae. In addition, 52.3% of the representative isolates had inhibitory properties against phytopathogenic fungi. Chemical analysis of one Streptomyces strain led to the discovery of two known compounds and one new compound. These results demonstrated that ant-derived actinobacteria represented an underexplored bioresource library of diverse and novel taxa that may be of potential interest in the discovery of new agroactive compounds.